Using mathematical modeling, identify the repetition and progression of the human eye's colour pattern - Ghani, Fahad; Syed, Asif Ali; Leghari, Irfan (Technium Education and Humanities, 2023)
The formation of human eyes is basically a result of genetic mutation process. The colour of eyes is determined by variation of genes which are associated with eye colour to produce transport or storage of a pigment is called melanin. In this research this aspect is confirm with the theory of Jordan algebra which has invented from an associative algebra which is relative to the arrangement, this scheme is called special Jordan algebras. To verifying the eyes colour mutation an appropriate number of datasets are collected from survey and observation, similar result found from the collected datasets which show that, the human eyes colour which is an outcome of genetic mutation of eye genes which appeared in first generation is mostly skip in second generation cycle and same process is repeat in generation to generations. The climate of Pakistan is usually varying in region to region because of temperature its dry and warm near the coastline and low-lying region and gradually cooler in the northern highland’s areas. Mostly in coldest area of Pakistan the colour of eyes are lighter but in some warm areas the lighter eyes colour in eyes colour in eyes causes different types of eyes disease. Lighter eye colour is more sensitive to light because of less amount of melanin. Melanin protects eyes from sun light due to lesser amount of melanin there is chances of macular degeneration (an eye disease that can blur your central vision). The darker coloured eyes practice less visual discomfort in sun light, mean it help in protection from ultraviolet (UV) rays. Lighter coloured of eyes increased the risk of cancer because of less amount of melanin which cannot/less protect eyes from sun light which is very harmful and increase the chance of cancer. Colour vision deficiency, sometime called colour blindness is usually a genetic (hereditary) condition transfer into next generation. Colour blindness is a cause of less melanin ration, the prediction of repetition of eye colour of next generation can be helpful to stop the problem of colour blindness.